In vitro studies on viability and proliferation of Enteromyxum scophthalmi (Myxozoa), an enteric parasite of cultured turbot Scophthalmus maximus - Redondo, Mª José; Palenzuela, Oswaldo; Álvarez-Pellitero, Mª del Pilar (Diseases of Aquatic Organisms, 2003)
In vitro cultivation of the myxozoan Enteromyxum scophthalmi was attempted using different culture media and conditions. The progress of the cultures was monitored using dye-exclusion viability counts, tetrazolium-based cell-proliferation assays, measuring the incorporation of BrdU during DNA synthesis, and by morphological studies using light and electron microscopes. In preliminary experiments, the persistence of viable stages for a few days was ascertained in both medium 199 (M199) and in seawater. An apparent initial proliferation was noticed in the culture media, with many young stages observed by Day 7 post-inoculation (p.i.). In contrast, fast degeneration occurred in seawater, with but a few living stages persisting to Day 1 p.i and none to Day 5 p.i. Both tetrazolium-based cell-proliferation assays and dye-exclusion viability counts demonstrated a progressive degeneration of the cultures. Although M199 medium and neutral pH with the addition of sera appeared to provide the most favourable conditions during the first few hours, all cultures degenerated with time and no parasite proliferation or maintenance could be achieved in the long term in any of the conditions assayed, including attempts of co-cultivation with a turbot cell line. The ultrastructure of stages cultured for 15 d demonstrated complete degeneration of organelles and mitochondria, although the plasma membrane remained intact in many stages. Unknown factors related to the metabolism or the life cycle of this myxozoan are probably responsible for the inability to culture the parasite, which seems to be strictly dependent on the target host tissues for survival. This study was financed by the EU and Spanish Government through the research grant FEDER 1FD97-0679-C02-01. Additional support was provided by Stolt Sea Farm, S.A. The authors are thankful to the Electron Microscopy Services from the Universities of Barcelona and Valencia.